Sundanese Values and Ideology on Film “Rocker Balik Kampung” (2018) by Uli Rahman - Jordy Satria Widodo (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
Film has been the means of communication. In addition, it has been recognized to be mediated quasi-interaction which shows a monological manner in term of the communication between the contents and the audience. It also can portray the representation of a certain culture in a particular country, specifically Indonesia. In addition to the local culture, Sundanese is the second ethnic majority that mostly dwell in the province of West Java. What is more, the ethnicity still shows rare portrayals on film since there are not many movies that incorporate the Sundanese culture into their stories. Rocker Balik Kampung (2018) by Uli Rahman is one of the films that integrates Sundanese culture to be the big theme. It focuses on a Sundanese rocker who has successfully made a living in the metropolitan city. Moreover, the chief of his village sends a messenger to look for him and bring him back to the village since he is going to get promoted to become the next chief in the village. Furthermore, he experiences dilemmas since he needs to encounter some protests from the notable village elder. This research was aimed at investigating Sundanese values and ideology on Rocker Balik Kampung (2018) by Uli Rahman. The research used qualitative approach through semiotics analysis by Roland Barthes. The analysis utilized denotation and connotation level of signs through various scenes on the film. The data collection technique was done using document analysis. The result showed that Somèah values and the ideology of Cageur, Bageur, Bener, Singer, and Pinter are really prominently depicted on the film.   Keywords: Sundanese; cultural values; ideolo